Organizational Commitment as a Moderator in the Relationship Between Transformational Leadership and Job Satisfaction: A Study of Banking Sector in Multan - Zara Hayat; Sahar Hayat; Shahzadi Sattar (Sustainable Business and Society in Emerging Economies)
Purpose: This study investigates the impact of transformational leadership on job satisfaction and organizational commitment among employees in the banking sector of Multan, Pakistan. It further examines the moderating role of organizational commitment in the relationship between transformational leadership and job satisfaction.